Analysis of Soybean Supplier Selection for MSMEs Tofu Tempe Using the Analytical Hierarchy Process (AHP) Method - Musthofa, Maschan Yusuf; Hakim, Luqman (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2023)
In the process of processing food products which are widely produced by home industries such as tofu and tempeh, one of the things that needs to be considered is procurement management which includes raw material purchasing activities. In raw material purchasing activities, supplier selection is an important process because it can help a business in terms of reducing raw material costs, inventory costs, and distribution costs as well as encouraging efficiency in terms of production time to product marketing. Therefore, this research will explain a tough and effective supply chain management system for conducting risk assessments in supply chain management, especially in home industries using distributed analysis, impact analysis, and failure modes. Using the Analytical Hierarchy Process (AHP) method can be a solution in solving the problem of decision-making for tofu and tempeh MSMEs in Kemantren Tulangan Village, Sidoarjo in selecting the best soybean supplier using the criteria of quality, price, delivery, and service, convenience, and relationships. This research was conducted using qualitative methods. This data collection technique uses interview techniques, observation, and literature study. Meanwhile, the sampling technique used snowball sampling technique, the informants consisted of 2 people, namely the Head of Production and Administration. Based on data processing using the AHP method using the Expert Choice application, it produces weighted values for each criterion, namely quality (0.165), price (0.228), delivery (0.114), service (0.144), convenience (0.201), and relationship (0.147). Meanwhile, the weighted values for each supplier are supplier 1 (0.413), supplier 2 (0.260), and supplier 3 (0.327). From the results of this data processing, the most important criterion in selecting the best supplier is the price criterion and the priority for the best supplier is supplier 1.